SAR Signal Reconstruction from Non-Uniform Displaced Phase Centre Sampling in the Presence of Perturbations - Gebert, Nicolas; Krieger, Gerhard; Moreira, Alberto (IGARSS International Geoscience and Remote Sensing Symposium, 2005)
The displaced phase centre (DPC) technique enables a wide swath SAR with high azimuth resolution. In classic DPC systems, the pulse repetition frequency (PRF), sensor velocity and antenna length underlie a stringent timing requirement and any deviation will result in a non-uniform sampling of the synthetic aperture. This restriction can be overcome by the use of a reconstruction algorithm, which enables a recovery of the unambiguous Doppler spectrum also in case of a non-uniform sampling. This paper explains limitations of the reconstruction imposed by the processing and the impacts on the ambiguity suppression. The potential of the algorithm when applied to DPC systems like TerraSAR-X with its split receive antenna is demonstrated and the benefits resulting from the additional receive aperture regarding swath width and resolution are pointed out. Further on, the impact of additive and phase noise on the reconstruction and its sensitivity against these perturbations are shown. © 2005 IEEE.
DLR Import::2019-04-03